Cognitive insight in psychotic patients institutionalized and living in the community: an examination using the Beck Cognitive Insight Scale - Pinho, Lara (2020)
Improving cognitive insight can reduce delusions in patients with psychotic disorders. Although institutionalized patients usually have more severe delusions than outpatients, little is known about the differences in cognitive insight between these two groups. In this study, we evaluated the psychometric properties of the Beck Cognitive Insight Scale (BCIS) for a sample of Portuguese patients with psychotic disorders and compared the cognitive insight of institutionalized patients with patients living in the community. Participants in this study were 150 patients diagnosed with psychotic disorder (78 institutionalized patients and 72 outpatients). The tested model of the BCIS was a very good fit. Our study shows that patients living in the community showed higher levels of cognitive insight (total BCIS and self-reflectiveness) than institutionalized patients. Future studies assessing cognitive insight should take into account differences between the cognitive insights of institutionalized psychotic patients and psychotic patients living in the community.